Avifauna costeiro-marinha do litoral de Sergipe : histórico de ocorrência e interação com vazamentos de óleo - Almeida, Bruno Jackson Melo de (2015)
The main goal of this thesis was to propose a bird oil vulnerability index (BOVI) in order to offer information about seabird species vulnerability for action planning and response strategy in case of oil spill disaster. To achieve this goal we shared interdisciplinary knowledge in environmental science with emphasis on ornithlogy, approaching laws and international regulamentation, in way to address a methodology baseline for the oil industry response emergency. We considered the coastline of Sergipe, state located at Northeast Brazil and the acquatic birds associated to the coastal environments. On the basis of the state of art of Bird literature published in Sergipe and field observations we recognized 114 species, which 54 were related to the coastal wetlands, 38 species were found on the beach environment and 66 species related to mangrove-estuarine habitats. The information about the seabirds were obtained from data analysis of environmental monitoring programs, specially from beach monitoring projects and offshore marine observation, thus indicating the occurrence of 45 seabirds species. Oiled bird information was evaluated from the dataset of stranding animals program result which indicated a low number of records compared to the total amount of stranding occurrence. This information is still diffuse and not related to oil spill in Brazil. The Magellanic penguin (Spheniscus magellanicus) was the specie more affected by oil (84%) for the records of the Campo-Espírito Santo Basin beach monitoring program. While for the Sergipe-Alagoas Basin monitoring program Manx shearwater (Puffinus puffinus) was the specie with more number of oiled individuals (62%). Despite the scarce information available it was possible to elaborate a table of categories describing specie/individual vulnerabilitity. The BOVI results presented Puffinus gravis, P. puffinus, Spheniscus magellanicus and Calonectris borealis as the species more vulnerable to oil incidence. We believe that better informations need to be colect, but there’s urgent for the standardizing of proceedings and technical cooperation between researchers and institutions.